Copper and its inorganic compounds [BAT Value Documentation, 2017]. Issue 1 (15th February 2018) - Letzel, S.; Roßbach, B.; Drexler, H.; Hartwig, A.; ,
Abstract: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has evaluated copper (CAS No 7440‐50‐8 ) in 2016. Due to the homeostatic regulation of copper there is no correlation between copper exposure in air and copper in blood or urine. Neither increased inhalation exposure higher than the MAK value of 0.01 mg copper/m 3 nor increased oral supply lead to an increase of copper in blood or urine, even if first signs of exposure such as increased C‐reactive protein (CRP) are observed. An additional occupational burden cannot be differentiated from physiological levels of copper. Therefore, the evaluation of a biological tolerance value (BAT value) and a biological reference value ("Biologischer Arbeitsstoff‐Referenzwert" (BAR)) for copper and its inorganic compounds is not indicated.